Application of model-based system engineering to a planetary rover design - Castaing, Hugo; Tang, Gilbert; Chacin, Marco; Bonnefoi, Fabien (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Traditional system engineering methods have shown their limits when applied to highly complex systems such as rovers. In parallel, the digitalisation of the industry and the democratisation of the use of models in engineering force the system engineering field to adapt and change its practices by adopting a new approach: Model-Based System Engineering. This project aimed to provide a comprehensive example of an MBSE approach applied to a planetary rover design case study. The MathWorks MBSE toolchain is used to reverse engineer the NASA Sojourner rover. As a result, the defined requirements, and functional and logical architectures are implemented and dynamically linked together. Additionally, a multi-physical simulation model of the rover's power and mobility system is implemented. Requirements, architectures, and physical models are linked together to form a unique and comprehensive knowledge base, providing a vertical model-centric approach. The results of the simulation are used to conduct a trade study and deduct a design change for the system. The results presented in this study form the basis for a discussion aimed at evaluating the benefits and limitations of the MBSE approach mentioned in the scientific literature.
Keywords: Model-based system engineering; system engineering; Planetary rover; Multi-physical simulation; Modelling; Simulink